2016
DOI: 10.3892/ol.2016.4266
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-34a by diallyl disulfide suppresses invasion and induces apoptosis in SGC-7901 cells through inhibition of the PI3K/Akt signaling pathway

Abstract: Abstract. Diallyl disulfide (DADS) exerts anticarcinogenic activity in various types of cancer. However, the mechanism underlying its anticarcinogenic activity remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…PI3K/AKT signaling pathway is deregulated in various cancers, which plays a key role in cell survival and proliferation, glucose metabolism, apoptosis, adhesion and metastasis (38). DADS was found to cause a significant reduction in the invasion of SGc-7901 cells by upregulating miR-34a, via the inhibition of the PI3K/AKT signaling pathway (39). Our data are consistent with this concept.…”
Section: Discussionsupporting
confidence: 84%
“…PI3K/AKT signaling pathway is deregulated in various cancers, which plays a key role in cell survival and proliferation, glucose metabolism, apoptosis, adhesion and metastasis (38). DADS was found to cause a significant reduction in the invasion of SGc-7901 cells by upregulating miR-34a, via the inhibition of the PI3K/AKT signaling pathway (39). Our data are consistent with this concept.…”
Section: Discussionsupporting
confidence: 84%
“…DADS can silence HIF-1α (hypoxia inducible factor 1α) via increasing expression of miR-22 to repress VEGF (vascular endothelial growth factor) expression to block angiogenesis, leading to the disruption of cancer progression [79,84]. The upregulation of miR-22 induced by DADS may post-transcriptionally target cyclin A2 and CDKN1A (cyclin-dependent kinase inhibitor 1A) to arrest the cell cycle in G0/G1 phage in CRC and liver cancer cells, respectively [85,86]. The recent researches have confirmed that DADS induces apoptosis of SGC-7901 cells by upregulation of miR-34a, via inhibition of the PI3K-Akt signaling pathway [87].…”
Section: Regulation Of the Mirnas By Dadsmentioning
confidence: 99%
“…Among these miRNAs, miR-34a is significantly downregulated in chemoresistant prostate cancer cell line (3) or CD44 + cancer stem cells (4). As a tumor suppressor miRNA, miR-34a is responsible for promoting tumor cell apoptosis, inhibiting tumor metastasis (5) and chemoresistance (6). Thus, miR-34a replenishment might be a novel therapeutic method to reverse PTX-resistance for the treatment of chemoresistant prostate cancer.…”
Section: Introductionmentioning
confidence: 99%